Open secrets : India's intelligence unveiled - Dhar, Maloy Krishna, 1937- (New Delhi : Manas Publications, 2005)
On life and work of an Indian intelligence officer.
Keywords: India. -- Intelligence Bureau; Intelligence service -- India; India -- Politics and government -- 1947-